Lotmanian Perspective on Complexity in Cultural Systems - Rickberg, Merit (Semiotika, 2022)
This article sets out to discuss the potential of Juri Lotman’s semiotic theory to serve as a ground from where a new understanding of cultural complexity could emerge. While the connection between Lotman and complex systems theory is quite well established, what is yet to be clarified is the ways in which his approach differs from the universally accepted understandings of complex dynamics, i.e., what makes Lotman’s perspective on complexity unique? The article also explores the possibility of developing Lotman’s ideas further in the context of the contemporary paradigm of complex thought with the aim of clarifying the specifics of complexity in cultural systems. In order to fill these aims, the article will first compare Juri Lotman’s ideas with a generally recognized understanding of complexity to delineate a common ground. Then, the paper will address the issue of how studying complexity differs in physical systems and cultural systems, focusing on how this matter has been discussed in semiotics. The final part of the article will propose some initial lines of thoughts regarding how Lotman’s ideas could be advanced further to grasp the phenomenon of complexity in culture.